Optimization of Production Benefits Through the Linear Program Graph Method: A Case Study Zentha Meubel - Hersiyati Palayukan (Mathematics Education Journal, 2021)
Production at Zentha Meubel is experiencing constraints due to the availability of wooden planks and the time spent making cabinets and tables. Meanwhile, the company wants to get optimal profit. To solve this problem, this study aims to utilize a linear graphical method program to optimize production profits at Mr. Andarias' Zentha Meubel. This research is a qualitative research type of phenomenology. The process carried out in optimizing the production is collecting data by interview and observation. Furthermore, a mathematical model is made and then optimizes the production profit using the graphical method. The results with the graph method show that production at Zentha furniture will achieve optimal results if it produces 15 units of cabinets with a profit of Rp. 18,750,000. The results of the optimization calculation using the graph method will increase the profit of Rp. 2,250,000.